2014
DOI: 10.1186/1471-2458-14-636
|View full text |Cite
|
Sign up to set email alerts
|

Sexual risk behavior among people living with HIV and AIDS on antiretroviral therapy at the regional hospital of Sokodé, Togo

Abstract: BackgroundSeveral studies on the sexual risk behaviors in sub-Saharan Africa have reported that the initiation of antiretroviral therapy leads to safer sexual behaviors. There is however a persistence of risky sexual behavior which is evidenced by a high prevalence of sexually transmitted infections among people living with HIV and AIDS (PLWHA). We sought to determine the factors associated with risky sex among PLWHA on antiretroviral therapy in Togo.MethodsAn analytical cross-sectional survey was conducted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
31
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 18 publications
(34 reference statements)
10
31
5
2
Order By: Relevance
“…The characteristics found in this population were similar to those of other national and international studies with people living with HIV, being predominantly adult males with low education and income (9,(11)(12) , heterosexual (2,7) , with the presence of sexual partners (13) , low drug use (13) , with good adherence to ART (13)(14) and low incidence of comorbidities (14) , where the majority chose to disclose the diagnosis of HIV infection only to family members (4,14) . In relation to the Stigma Scale, the highest mean distribution values of means and medians in the disclosure domain were similar to those of another study with adults living with HIV (10) , and one performed with young American adolescents and young adults recently diagnosed with HIV (15) , showing that seropositivity disclosure is still an important difficulty experienced by HIV positive people (4,9) marked by fear of non-acceptance, as well as feelings of guilt and shame (5,9) .…”
Section: Discussionsupporting
confidence: 58%
“…The characteristics found in this population were similar to those of other national and international studies with people living with HIV, being predominantly adult males with low education and income (9,(11)(12) , heterosexual (2,7) , with the presence of sexual partners (13) , low drug use (13) , with good adherence to ART (13)(14) and low incidence of comorbidities (14) , where the majority chose to disclose the diagnosis of HIV infection only to family members (4,14) . In relation to the Stigma Scale, the highest mean distribution values of means and medians in the disclosure domain were similar to those of another study with adults living with HIV (10) , and one performed with young American adolescents and young adults recently diagnosed with HIV (15) , showing that seropositivity disclosure is still an important difficulty experienced by HIV positive people (4,9) marked by fear of non-acceptance, as well as feelings of guilt and shame (5,9) .…”
Section: Discussionsupporting
confidence: 58%
“…In a study in Uganda on HIV-positive people, the overall spread of safe sexual behaviours was 54.1%, and there wasn't a signif icant difference between female (56.3%) and male (51.3%) (p<0.131) (Bajunirwe 2013). In a study, 60% of HIV positive that take ARTs revealed safe sexual behaviours and 34% had high-risk sexual behaviours (Yaya ., 2014). Stein (2010) showed that a very few number of male participants had safe sex behaviours.…”
Section: Resultsand Discussionmentioning
confidence: 99%
“…Success in AIDS treatment by antiretroviral drugs (HAART) increased the span and life quality of HIVpositive patients, however, the increment of their life span let to continuing their sexual relations due to which the chances of unsafe sexual practices also increase among HIV-positive people. Thus, the number of registered cases related to sexual transmission of HIV are continuously increasing (Yaya , 2014). Nevertheless, the drug injection consumers are also sexually active and their sexual practices are also unprotected (Wood , 2013).…”
Section: Abstract Introductionmentioning
confidence: 99%
“…Fifty percent were injectable drug users a month prior to the study, and 33 percent of them had shared needles [4]. Unsafe sexual behaviors especially inconsistent condom use are practiced by the PLWHA as a significant proportion of this group remains sexually active [7] [8] [9]. The rate of HIV transmission per sexual act was found to be significantly higher among Men Having Sex with Men, MSM, than the heterosexual population [10].…”
Section: Introductionmentioning
confidence: 99%